Endogenous microbiota of the vagina. Diagnostics and principles of dysbiotic process' correction - S V Rishchuk; N A Tatarova; M S Airapetyan (IP Berlin A.V., 2014)
The article presents the terminology and modern views on the microbiota of the vagina. The characteristic of endogenous and exogenous trigger factors leading to the violation of vaginal microbiocenosis are also being discussed. Special attention is paid to the endocrine and immune regulation of endogenous microbiota of the vagina and affectation by its mechanisms, as well as the connection between endogenous microorganisms and pathogens of exogenous genital infections. The characteristic of varieties of dysbiosis of vagina, stages of development of endogenous infection and its clinical manifestations are mentioned below as well, as are various diagnostic approaches and principles of endogenous infection treatment.